Literature Review: Factors Associated with the Incident of Hypertension - Azizah, Nur; Abdullah, Rezky Putri Indarwati; Umar, Mahdi (Formosa Journal of Science and Technology, 2024)
Hypertension may be a major wellbeing issue that contributes to cardiovascular infection and other complications. Hypertension or tall blood weight is when the systolic weight is ≥140 mmHg, and the diastolic weight is ≥90 mmHg. Components that impact the event of hypertension are isolated into two expansive bunches, specifically variables that cannot be controlled such as sexual orientation, age, hereditary qualities, race and variables that can be controlled such as count calories, work out propensities, utilization of salt, coffee, liquor and stretch. The point of this article is to decide the variables related with the frequency of hypertension. In this writing, it was found that an increment in blood weight that endures for a long time, in case not identified and gotten satisfactory treatment, will cause harm to the kidneys, heart, brain and others. So to control hypertension it is necessary to require activities such as wellbeing advancement in arrange to preserve, progress and ensure individual wellbeing and environmental conditions. There are two chance components for hypertension, specifically chance components that cannot be changed, counting age, sex, hereditary qualities and hazard components that can be changed, counting smoking, moo fiber count calories, dyslipidemia, intemperate salt utilization, need of physical action, stretch, overabundance body weight/ corpulence and liquor utilization. A few variables that impact the frequency of hypertension incorporate components (age, sex), weight from drugs (steroids, painkillers), and comorbid characteristics.